Exploring lymphocyte subsets in COVID-19 patients: insights from a tertiary academic medical center with a high proportion of patients on immunosuppression - Daenen, Katrijn; van Hooijdonk, Samantha; Tong-Minh, Kirby; Dik, Willem A.; van Hagen, Petrus M.; Huijben, Jilske A.; Gommers, Diederik; van Gorp, Eric C. M.; Endeman, Henrik; Dalm, Virgil A. S. H. (Frontiers in Immunology, 2024)
IntroductionSevere COVID-19 is associated with reduced absolute lymphocyte counts, suggesting that lymphocyte subsets may serve as predictors of clinical outcomes in affected patients. Early identification of patients at risk for severe disease is crucial for optimizing care, accurately informing patients and their families, guiding therapeutic interventions, and improving patient flow in the ED. Given that immunosuppressive drugs significantly impact lymphocyte profiles, we aimed to determine the association between prior use of immunosuppressive drugs, lymphocyte subsets, and COVID-19 severity in our population with a high prevalence of immunosuppression.MethodsIn 2021, suspected COVID-19 patients were included in the ED. Lymphocyte subsets were determined in peripheral blood within 24 hours after presentation and comparative analyses was performed between SARS-CoV-2 negative and positive patients, mild versus severe disease and patients with and without prior immunosuppressive drug use. Mild cases were patients discharged home or admitted to a general ward, severe cases were patients with COVID-19-related mortality or necessitating ICU admission. Logistic regression analysis was performed to assess the association between lymphocyte subsets and COVID-19 severity, and between prior immunosuppressive drug use and COVID-19 severity.ResultsTwenty-five SARS-CoV-2 negative and 77 SARS-CoV-2 positive patients were included, whereof 57 (74%) had mild and 20 (26%) severe COVID-19. No significant differences were observed in the absolute counts of CD3+, CD4+, and CD8+ T-lymphocytes, B-lymphocytes, and NK-cells between SARS-CoV-2 negative and positive patients or between mild and severe cases. The 36 patients with prior use of immunosuppressive drugs had significantly lower CD4+ T-lymphocytes (p<0.01). Prior use of immunosuppressive drugs was not associated with COVID-19 severity (adjusted OR 1.074, 0.355-3.194).ConclusionLymphocyte subsets were not significantly different between SARS-CoV-2 negative and positive patients and between mild versus severe cases. Neither lymphocyte subsets nor prior immunosuppressive drug use were associated with COVID-19 severity.